Risk Factors Associated With Polypharmacy and Potentially Inappropriate Medication Use in Ambulatory Care Among the Elderly in the United States: A Cross-Sectional Study - Khue Nguyen; Vinita Subramanya; Ambar Kulshreshtha (Adis, Springer Healthcare, 2023)
Abstract Introduction Polypharmacy, defined as the concurrent use of multiple (commonly five or more) prescription drugs, is widely prevalent among the elderly. It is a preventable and significant contributor to morbidity and mortality among older people. It is linked to prescribing potentially inappropriate medications (PIMs), which have been shown to be associated with an increased risk of adverse drug interactions and reduced compliance, and in some cases result in prescribing cascades where more drugs are prescribed to manage adverse outcomes. This study aimed to examine risk factors associated with polypharmacy and PIMs among elderly patients in outpatient settings in the US. Methods We conducted a cross-sectional analysis using the nationally representative National Ambulatory Medical Care Survey, between 2010 and 2016. We extracted data from all people aged 65 years or older and evaluated factors associated with polypharmacy and PIMs using multivariable logistic regression. Weights were applied to obtain national estimates. Results During the study period, there were a total of 81,295 ambulatory visits among adults 65 years and older. Being a woman (compared with a man) was more likely to be associated with greater prevalence of PIMs (OR: 1.31, 95% CI 1.23-1.40), and living in rural areas were more likely to be associated with both polypharmacy (OR: 1.15, 95% CI 1.07-1.23) and PIMs (OR: 1.19, 95% CI 1.09-1.29), compared with living in urban areas. Older age was positively associated with polypharmacy (OR: 1.08, 95% CI 1.06-1.10), but negatively associated with PIMs (OR: 0.97, 95% CI 0.95-0.99). Conclusions Our study suggests age, being a woman, and living in rural areas are risk factors for both polypharmacy and PIMs usage. Aside from primary care providers' roles in managing polypharmacy, collaborative care with other specialty providers, such as clinical pharmacists, should also be considered as an approach to improving the quality of prescribing in geriatric patients. Future research should further explore reasons for polypharmacy and focus on deprescribing and quality improvement initiatives in primary care to lower polypharmacy among the elderly